EFEKTIVITAS MODEL PEMBELAJARAN TWO STAY TWO STRAY DENGAN TUTOR SEBAYA DALAM PEMBELAJARAN MATEMATIKA PADA MATERI BANGUN DATAR DITINJAU DARI KECERDASAN MAJEMUK PESERTA DIDIK KELAS VII SMP NEGERI DI KEBUMEN TAHUN PELAJARAN 2013/2014 - Miftachudin, Miftachudin; Budiyono, Budiyono; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of this research was to know the effect of the learning models on the learning achievement of quadrangle viewed from the multiple inellegences of the students. The learning models compared were the cooperative learning models of the TSTS type with peer tutor, the cooperative learning models of the TSTS type, and the direct learning models. The kind of research is quasi-experimental research with factorial design 3x3. Population of this research is all students of State Junior High Schools in Kebumen. The sample of this research is 288 students which is 95 students in Experiment I class, 96 students in Experiment II class, and 97 students in controlled class. The hypothesis test uses two ways analysis of variance with unbalanced cells. The result of the research shows that: (1) TSTS learning model by peer tutor shows the higher achievement of students than cooperative learning model of TSTS. The cooperative learning model of TSTS results as good as the direct learning model, and TSTS learning model by peer tutor results higher achievement than the direct learning one, (2) students with logic-mathematic linguistic, and interpersonal intelligence have the same achievement among them, (3) at TSTS learning model by peer tutor, TSTS learning model, and direct learning model, students with logic-mathematic, linguistic, and interpersonal intelligence have the same result, (4) at students with logic-mathematic, linguistic, and interpersonal intelligence, TSTS learning model by peer tutor results higher achievement than TSTS cooperative learning model; TSTS cooperative learning model results as good as the result of direct learning model; and TSTS learning model by peer tutor results higher achievement than the direct learning model.Keywords: TSTS learning model by peer tutor, Two Stay Two Stray, achievement, intelligence